THE CONTRADITORY AS A CONDITION FOR THE POSSIBILITY OF THE REFEREE’S INSTRUCTORY POWERS (Anais do Congresso Brasileiro de Processo Coletivo e Cidadania, 2020)
This article intends to analyzes whether the referee’s instructive powers must observe all dimensions of the adversarial principle, including those not expressly provided for in the Arbitration Law, in particular the guarantee of participation of the parties with influence and the prohinition of a surprise decision. In addition, it will be verified whether the basis for the possible applicability of such dimensions stems from art. 10 of the Civil Procedure Code or directly from art. 5º, LV, of the Federal Constitution, because, depending on the reasoning developed, the conclusion may be diferent, one not to be dealt with and the other not to be dealt with as conditions of possibility of the referee’s instructive powers. For the development of this work, na eminently bibliographic and jurisprudential research will the developed, with the objective of analyzing criticizing the proposed theme, in the light of the deductive method.